(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
Effective monitoring of protected natural areas is a critical prerequisite for biodiversity conservation, ecosystem sustainability, and evidence-based environmental management [1,2]. However, many existing monitoring systems remain fragmented, episodic, and weakly integrated with modern geospatial and analytical technologies, which limits their ability to detect spatial–temporal changes and emerging ecological risks in a timely manner